Lenvatinib in Patients With Advanced Grade 1/2 Pancreatic and Gastrointestinal Neuroendocrine Tumors: Results of the Phase II TALENT Trial (GETNE1509). Issue 20 (10th July 2021) - Capdevila, Jaume; Fazio, Nicola; Lopez, Carlos; Teulé, Alexandre; Valle, Juan W.; Tafuto, Salvatore; Custodio, Ana; Reed, Nicholas; Raderer, Markus; Grande, Enrique; Garcia-Carbonero, Rocio; Jimenez-Fonseca, Paula; et al.
Abstract : PURPOSE: Approved systemic therapies for advanced gastroenteropancreatic neuroendocrine tumors (GEP-NETs) have shown limited capacity to reduce tumor burden and no antitumor activity after progression to targeted agents (TAs). We investigated the efficacy and safety of lenvatinib in patients with previously treated advanced GEP-NETs. PATIENTS AND METHODS: This was a multicenter, single-arm, open-label, phase II trial with two parallel cohorts (ClinicalTrials.gov identifier: NCT02678780 ) involving 21 institutions in 4 European countries. Eligible patients had histologically confirmed advanced grade 1-2 pancreatic (panNET) or GI (GI-NET) NETs with documented tumor progression after treatment with a TA (panNET) or somatostatin analogs (GI-NET). Patients were treated with lenvatinib 24 mg once daily until disease progression or treatment intolerance. The primary end point was overall response rate by central radiology review. Secondary end points included progression-free survival, overall survival, duration of response, and safety. RESULTS: Between September 2015 and March 2017, a total of 111 patients were enrolled, with 55 (panNET) and 56 (GI-NET) patients in each cohort. The median follow-up was 23 months. The overall response rate was 29.9% (95% CI, 21.6 to 39.6): 44.2% (panNET) and 16.4% (GI-NET). The median (range) duration of response was 19.9 (8.4-30.8) and 33.9 (10.6-38.3) months in the panNET and GI-NET groups, respectively. The median progression-free survival was 15.7 months (95% CI, 14.1 to 19.5). The most common adverse events were fatigue, hypertension, and diarrhea; 93.7% of patients required dose reductions or interruptions. CONCLUSION: We report the highest centrally confirmed response reported to date with a multikinase inhibitor in advanced GEP-NETs, with a particularly strong response in the panNET cohort. This study provides novel evidence for the efficacy of lenvatinib in patients with disease progression following treatment with other TAs, suggesting the potential value of lenvatinib in the treatment of advanced GEP-NETs.